TRANSFORMASI SOSIAL EKONOMI PEDAGANG DI PASAR SEKITARAN JAM GADANG - Dinda Rahmayani Fatma; Fatmariza Fatmariza (STKIP Pesisir Selatan, 2026)
The Jam Gadang area in Bukittinggi City serves as the tourism epicentre and the primary driver of the regional economy in West Sumatra. Post-pandemic infrastructure modernization, spatial restructuring, and massive digitalization have triggered significant socio-economic transformations for the surrounding local merchant community. This study aims to analyze the socio-economic characteristics and dissect the forms of transformation occurring among merchants in the Jam Gadang area. Utilizing a descriptive qualitative approach, data were gathered through passive participant observation, documentary studies, and in-depth interviews with various merchant typologies (apparel, culinary, mobile fruit vendors, and general commodities). The results indicate that the current merchant profile is dominated by productive-age individuals with upper-secondary education and high technological adaptability. Economic transformation is highly evident in the mass migration toward digital payment systems (QRIS) and omnichannel marketing (social media), which has successfully driven upward vertical mobility for apparel and souvenir food vendors. However, this transformation has also induced economic inequality (income degradation) for tech-illiterate non-souvenir merchants, alongside the restriction of social spaces for mobile informal vendors due to the enforcement of zoning regulations. Despite tightening competition, the persistence of social capital rooted in Minangkabau kinship values through market associations proves to be a critical safety valve for merchant resilience. The Bukittinggi Municipal Government is advised to formulate humane spatial policies and inclusive digital literacy assistance to ensure that the growth of the tourism sector is equitably distributed.